Forearm Compartment Syndrome Caused by Reperfusion Injury - Ufuk Sayar; Tanıl Özer; İlker Mataracı (Case Reports in Vascular Medicine)
Compartment syndrome is commonly seen following lower extremity ischemia. However, upper extremities’ compartment syndrome, especially after any vascular surgical procedures, is infrequent. Herein we report a case of an acute forearm compartment syndrome that was developed after delayed brachial artery embolectomy.